Life satisfaction and resilience in medical school – a six-year longitudinal, nationwide and comparative study - Gronvold Nina T; Gude Tore; Hem Erlend; Finset Arnstein; Tyssen Reidar; Kjeldstadli Kari; Ekeberg Oivind; Vaglum Per (BMC Medical Education, 2006)
Abstract Background This study examined the relationship between life satisfaction among medical students and a basic model of personality, stress and coping. Previous studies have shown relatively high levels of distress, such as symptoms of depression and suicidal thoughts in medical undergraduates. However despite the increased focus on positive psychological health and well-being during the past decades, only a few studies have focused on life satisfaction and coping in medical students. This is the first longitudinal study which has identified predictors of sustained high levels of life satisfaction among medical students. Methods This longitudinal, nationwide questionnaire study examined the course of life satisfaction during medical school, compared the level of satisfaction of medical students with that of other university students, and identified resilience factors. T-tests were used to compare means of life satisfaction between and within the population groups. K-means cluster analyses were applied to identify subgroups among the medical students. Analysis of Variance (ANOVA) and logistic regression analyses were used to compare the subgroups. Results Life satisfaction decreased during medical school. Medical students were as satisfied as other students in the first year of study, but reported less satisfaction in their graduation year. Medical students who sustained high levels of life satisfaction perceived medical school as interfering less with their social and personal life, and were less likely to use emotion focused coping, such as wishful thinking, than their peers. Conclusion Medical schools should encourage students to spend adequate time on their social and personal lives and emphasise the importance of health-promoting coping strategies.